The Thrombin Activation Pathway Modulates the Assembly, Structure and Lysis of Human Plasma Clots In Vitro - Torbet, Jim (Thrombosis and Haemostasis, 1995)
Thrombin activation of the soluble plasma protein fibrinogen is vital for successful haemostasis. Thrombin is generated from prothrombin by the prothrombinase complex which also includes factor Xa, factor Va, Ca2+ and a procoagulant membrane surface. Factor X activation is catalysed in a complex including either factor Vila and tissue factor, or factor IXa and factor Villa. Factor IXa can be generated either by the factor Vlla/tissue factor complex or by factor XIa which is in turn produced by the contact phase reactions in vitro. Once activated, fibrinogen develops into the fibrin polymeric matrix at the site of injury. It is not known to what extent the properties of this haemostatic plug are sensitive to the pathway leading up to thrombin generation. Here static human plasma is studied in vitro using magnetically induced birefringence. It is shown that the contact phase/factor XIa pathway gives rise to linear fibrin assembly progress curves whereas the factor Vlla/tissue factor activation of factor X provokes largely sigmoid assembly. The latter pathway also causes the formation of significantly thicker fibres even although assembly is more rapid. This result is the inverse of that anticipated from the study of simple model systems. Whilst the streptokinase activated lysis of both types of clot exhibits similar biphasic kinetics, an exponential main phase followed by a sigmoidal tailing off, the data suggest that clots produced by the contact phase/factor XIa pathway are more recalcitrant to lysis. These results demonstrate that the profile of thrombin generation not only determines the kinetics of assembly but also influences the rate of lysis and structure of the haemostatic plug.